CRITICAL HEAT FLUX NANOFLUIDS MEASUREMENTS SYSTEM USING ARDUINO - Santiko Tri Sulaksono; Sudjatmi Kustituantini Alfa; Dani Gustaman Syarif (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2021)
Crtical heat flux (CHF) is an important characteristic of nanofluids. The CHF measurements were carried out in nanofluid research at the Center for Applied Nuclear Science and Technology. These measurements are done manually using a variable power supply and a multimeter. However, it was difficult to record the voltage and current due to the sudden break of the wire. In this study, Arduino was used to measure CHF automatically. The voltage is applied to the wire and increases automatically along with the measurement of the voltage and current in the wire. The results of the voltage and current measurements were compared with a multimeter and were not significantly different. It can be concluded that the CHF measurement system using arduino can be used to measure nanofluid CHF.